Spatial and Temporal Analysis of Skipjack Tuna (Katsuwonus pelamis) Catch and Thermal Front during the Transition Season in the Bone Bay - Nur Indah Rezkyanti, Nur; Anggreini, Anggerini; Safruddin, Saffruddin; Mukti Zainuddin, Mukti (Journal IPTEKS Pemanfaatan Sumberdaya Perikanan, 2014)
The main problem facing by fishermen for capturing skipjack tuna is limited information of potential skipjack fishing areas such as the frontal locations. The purpose of this study was to analyze the spatial and temporal skipjack tuna distributions and thermal fronts, and to determine the effect of climate change on their distribution and abundance during transitional seasons. We used a survey method, in which catch and fishing position data were collected by following pole and line fishing operations. This study also collected secondary data that consisted of sea surface temperatures (SSTs) and chlorophyll-a derived from Aqua / MODIS. Fronts were determined by calculating SST gradient, SSTs preferences, chlorophyll-a, bathymetry and distance from coastline, whereas SST anomaly was calculated from the difference between monthly SST and mean SST. We mapped satellite and field data using ArcGIS 10.0.Â The results showed that the highest catch of skipjack tuna with an average of 205 fish/set were found in October 2013, which occurred in the areas of 4o40S-5o10S and 120o40E-121oE. The locations had a temperature gradient of 0.4oC and chlorophyll-a density from 0,15 to 0,23 mg m-3. Potential fishing areas may associate with negative SST anomalies of -2.1373 - -0.6469oC, reflecting that skipjack tuna tend to be at thermal fronts with relatively lower SST compared with an average of seven years.